Brentuximab Vedotin in Patients With Hodgkin Lymphoma and a Failed Allogeneic Stem Cell Transplantation: Results From a Named Patient Program at Four Italian Centers. (10th February 2015) - Carlo-Stella, Carmelo; Ricci, Francesca; Dalto, Serena; Mazza, Rita; Malagola, Michele; Patriarca, Francesca; Viviani, Simonetta; Russo, Domenico; Giordano, Laura; Castagna, Luca; Corradini, Paolo; Santoro, Armando
Abstract: Background: Brentuximab vedotin (BV) has demonstrated an extraordinary efficacy in heavily pretreated classical Hodgkin lymphoma (cHL) patients, targeting CD30-positive cells; however, limited data have been reported on the efficacy of BV in cHL patients failing allogeneic stem cell transplantation (allo-SCT). The aim of this study was to retrospectively evaluate the efficacy and safety of BV in a multicenter setting of cHL relapsing or progressing after allo-SCT. Methods: Sixteen BV-naïve patients with recurrent cHL after allo-SCT were included in a compassionate use program and treated with intravenous BV at the dose of 1.8 mg/kg of body weight every 3 weeks for a maximum of 16 cycles. Results: The objective response rate was 69%. Five patients (31%) had complete remission, and 6 (37%) had partial remission. Stable disease was observed in 4 patients (25%), and progressive disease was observed in 1 (6%). After median follow-up of 26 months (range: 5–30 months), median progression-free survival (PFS), overall survival (OS), and duration of response were 7, 25, and 5 months, respectively. The 2-year PFS and OS were 20% and 61%, respectively. Grade 3–4 hematological adverse events included anemia (15%), thrombocytopenia (12%), and neutropenia (18%). Grade 3 peripheral sensory neuropathy occurred in 2 patients (12%). Conclusion: BV therapy is an effective and safe approach for achieving transient disease control in cHL patients with failed allo-SCT. To improve disease control, future studies should explore the combination of BV with targeted agents. Abstract : The aim of this study was to retrospectively evaluate the efficacy and safety of brentuximab vedotin (BV) in a multicenter setting of classical Hodgkin lymphoma relapsing or progressing after allogeneic stem cell transplant. Results showed that BV therapy is an effective and safe approach for achieving transient disease control in these patients. To improve disease control, future studies should explore the combination of BV with targeted agents.